ENVIRONMENTAL AND SPATIAL FACTORS ARE POOR PREDICTORS OF FISH BETA DIVERSITY IN CERRADO STREAMS - Oliveira, Fagner Junior Machado de (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2023)
Beta diversity, the spatial or temporal variation in community structure, is a central themein community ecology. In this study, we evaluated the explanatory power of environmental and spatialvariables in predicting fish beta diversity. Using data from Cerrado streams, we first partitioned fishbeta diversity into three components using both presence-absence (total, turnover, and nestedness) andabundance data (total, balanced changes in abundance, and abundance gradients). Then, we evaluatedthe individual influences of environmental and spatial variables on each of these components. Our resultsshowed that environmental and spatial variables explained significant fractions of variation in fish betadiversity. However, most of the variation in total beta diversity and its components remained unexplained.Considering presence-absence data, significant fractions were obtained only for total beta diversity. Forthis type of data, spatial variables were more important than environmental variables. Abundance-basedanalyses showed that both total beta diversity and its components (balanced changes in abundanceand abundance gradients) were explained by environmental and spatial variables. With abundancedata, environmental and spatial variables were similarly related to total beta diversity and balancedchanges in abundance, while spatial variables were the sole predictors of the abundance gradients.Despite methodological and theoretical advances in beta diversity studies, we still need to seek relevantenvironmental, spatial, temporal, and biological data that explain beta diversity patterns in streams.